Pulmonary embolism and infarction with a paradoxical thrombus visualised in both atria. (30th May 2018) - Zafar, Hamza; Anderson, Lisa; Cox, Andrew T; Bastiaenen, Rachel
Abstract : A 59-year-old woman presented with a sudden onset of breathlessness and chest pain. An echocardiography and CT scan showed pulmonary embolism and infarction with a paradoxical thrombus visualised in both atria. For haemodynamically stable patients, the optimal management strategy is poorly defined. Three main strategies were considered: surgical thrombectomy, thrombolysis and anticoagulation. Surgery with reversal of anticoagulation may lead to further coagulation and increased risk of bleeding complications. The significant pulmonary hypertension and right ventricular infarction raised the prospect of difficult weaning from cardiopulmonary bypass following thrombectomy. Thrombolysis, which has significant mortality rate, and systemic embolisation including pulmonary infarction with haemorrhagic transformation were also contraindications. A multidisciplinary approach was adopted and anticoagulation was therefore believed to be the safest and effective approach. Here, the use of anticoagulation alone was fortunately successful but could as easily end in disaster. This approach should be considered the ideal paradigm to yield optimum outcomes.